2016
DOI: 10.1242/jeb.131714
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced phenotypic plasticity in European eel (Anguilla anguilla)

Abstract: Two phenotypes are present within the European eel population: broad-heads and narrow-heads. The expression of these phenotypes has been linked to several factors, such as diet and differential growth. The exact factors causing this dimorphism, however, are still unknown. In this study, we performed a feeding experiment on glass eels from the moment they start to feed. Eels were either fed a hard diet, which required biting and spinning behavior, or a soft diet, which required suction feeding. We found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Resource polymorphism can arise through developmental plasticity within a homogenic population, by natural selection on genetically encoded traits or a combination of these mechanisms. For instance, the broad and narrow‐headed morphs of the European eel ( Anguilla anguilla ) were found to be determined to a large extent by diet (De Meyer, Christiaens, & Adriaens, ) and ecomorphs of killer whales ( Orcinus orca ) were hypothesized to have originated through plastic responses of a small founder population (Foote et al, ). Examples of genetically determined resource polymorphism can be found in crater lake cichlid fishes, for example, were a single locus effects jaw and body shape (Fruciano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Resource polymorphism can arise through developmental plasticity within a homogenic population, by natural selection on genetically encoded traits or a combination of these mechanisms. For instance, the broad and narrow‐headed morphs of the European eel ( Anguilla anguilla ) were found to be determined to a large extent by diet (De Meyer, Christiaens, & Adriaens, ) and ecomorphs of killer whales ( Orcinus orca ) were hypothesized to have originated through plastic responses of a small founder population (Foote et al, ). Examples of genetically determined resource polymorphism can be found in crater lake cichlid fishes, for example, were a single locus effects jaw and body shape (Fruciano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, our results provide support for the third hypothesis that a combination of genetic differences and environment‐dependent developmental plasticity drives head shape dimorphism. On the one hand, there is definite support that differences in head shape are related to dietary differences in the elver and yellow eel stage (De Meyer et al., ). On the other hand, we found that the genes somatotropin‐1 (or GH1 ) and igf2 were significantly upregulated in narrow‐heads.…”
Section: Discussionmentioning
confidence: 99%
“…() showed that narrow‐headed yellow eels have a significantly lower trophic position than broad‐headed ones based on stable isotope analysis, independent of their body size. Finally, a study by De Meyer, Christiaens, and Adriaens () showed that elver eels developed a broad‐head when given hard food, whereas elvers fed soft food retained a narrow‐head, soon after pigmentation started. Consequently, head shape might be solely a plastic response to dietary differences.…”
Section: Introductionmentioning
confidence: 99%
“…; De Meyer et al. ). Their diet mainly consists of harder prey items, such as large crustaceans and fish, whereas that of narrow‐headed phenotypes generally includes small invertebrates such as insect larvae.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, De Meyer et al. () showed that dietary differences in the latter stage can stimulate the development of more extreme broad and narrow heads, with eels still being smaller than 15 cm.…”
Section: Introductionmentioning
confidence: 99%